2009
DOI: 10.1159/000261789
|View full text |Cite
|
Sign up to set email alerts
|

An Adhesion Barrier May Induce Peritonitis and Abscess after Laparoscopy-Assisted Myomectomy with Vaginal Extraction: Report of a Case

Abstract: Following a myomectomy, postoperative adhesions occur in many patients. Although laparoscopy has been shown to decrease the development of adhesions compared to laparotomy, adhesions still occur. There are several commercially available adhesion barriers but these are not designed to be easily applied during laparoscopic surgery. In this study, we report a case involving a 34-year-old patient who developed pelvic peritonitis and abscess without an obvious etiology; this might have been related to the off-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Consistent with our results, most previous studies have reported that postoperative infections were not related to posterior colpotomy and transvaginal extraction [ 14 16 ]. Conversely, the complication of vaginal abscess has been reported after transvaginal NOSE procedure following laparoscopic myomectomy [ 17 , 18 ]. However, the authors explained that the abscess could be attributed to the adhesion barrier used during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, most previous studies have reported that postoperative infections were not related to posterior colpotomy and transvaginal extraction [ 14 16 ]. Conversely, the complication of vaginal abscess has been reported after transvaginal NOSE procedure following laparoscopic myomectomy [ 17 , 18 ]. However, the authors explained that the abscess could be attributed to the adhesion barrier used during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of adhesion formation after peritonitis seems the ultimate challenge for proving the effectiveness of an anti-adhesion barrier. It also is crucial that the barrier does not promote infection or abscess formation [17,18].…”
mentioning
confidence: 99%
“…Moreover, the authors concluded that the risk of pelvic infection was not an adequate reason to avoid a colpotomy for pelvic mass retrieval . Two case reports demonstrated that vaginal abscesses developed following laparoscopic myomectomies with TV retrievals . The authors indicated that these complications could be attributed to the adhesive barrier that was used in both operations.…”
Section: Discussionmentioning
confidence: 99%